Profile of children with pleural effusion in an urban tertiary care hospital - Saliya, Maulik P.; Joshi, Gurudutt S. (International Journal of Contemporary Pediatrics, 2017)
Background: Management of pleural effusions depends on their origin whether exudates or transudates, simple or complicated with septations and pneumonia. A complicated effusion requires longer treatment. This study was carried out to find out types of effusion and their etiology. Methods: A Prospective study of 34 patients was analyzed for clinical and laboratory profile, origin and type of fluid, etiology of pleural effusion in pediatric patients. Results: Majority of the patients were in 6-11 years age group. Fever and cough were most common clinical symptoms in all type of effusion. Parapneumonic effusion was most common type of effusion followed by tuberculosis and empyema. Almost all exudates satisfied Lights criteria. Conclusions: Pleural effusions are mostly exudative in origin in pediatric age and are associated with consolidation and septations especially in empyema. In tubercular Pleural effusion, Sputum for AFB was positive in more number of patients as compared to CBNAAT in this study.